Halotropism requires phospholipase Dζ1‐mediated modulation of cellular polarity of auxin transport carriers. (2nd October 2019) - Korver, Ruud A.; van den Berg, Thea; Meyer, A. Jessica; Galvan‐Ampudia, Carlos S.; ten Tusscher, Kirsten H.W.J.; Testerink, Christa
Abstract: Endocytosis and relocalization of auxin carriers represent important mechanisms for adaptive plant growth and developmental responses. Both root gravitropism and halotropism have been shown to be dependent on relocalization of auxin transporters. Following their homology to mammalian phospholipase Ds (PLDs), plant PLDζ‐type enzymes are likely candidates to regulate auxin carrier endocytosis. We investigated root tropic responses for an Arabidopsis pldζ1‐ KO mutant and its effect on the dynamics of two auxin transporters during salt stress, that is, PIN2 and AUX1. We found altered root growth and halotropic and gravitropic responses in the absence of PLDζ1 and report a role for PLDζ1 in the polar localization of PIN2. Additionally, irrespective of the genetic background, salt stress induced changes in AUX1 polarity. Utilizing our previous computational model, we found that these novel salt‐induced AUX1 changes contribute to halotropic auxin asymmetry. We also report the formation of "osmotic stress‐induced membrane structures." These large membrane structures are formed at the plasma membrane shortly after NaCl or sorbitol treatment and have a prolonged presence in a pldζ1 mutant. Taken together, these results show a crucial role for PLD ζ1 in both ionic and osmotic stress‐induced auxin carrier dynamics during salt stress. Abstract : This work shows that both ionic and osmotic stress affect auxin carrier dynamics during salinity stress, a response that requires the action of the phospholipase PLD ζ1 . Mathematical modelling shows that impaired cellular polarity in roots of pldζ1 seedlings explains their different halotropism (salt avoidance) response.